Carbon ceramic brake disc with stable friction coefficient and preparation method thereof
The addition of fillers and a reactive melt infiltration process stabilizes the friction coefficient and reduces wear in carbon-ceramic brake discs, enhancing braking stability and safety.
Patent Information
- Application Number
- CN202411138123.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-31
AI Technical Summary
Existing carbon-ceramic brake discs suffer from friction coefficient jitter, unstable braking, and excessive wear due to the 'plowing' effect and adhesive wear caused by high SiC content, which affects braking stability and safety.
A method involving the addition of fillers like multi-walled carbon nanotubes, graphite powder, or molybdenum disulfide, combined with a slurry impregnation and reactive melt infiltration process, to create a carbon-ceramic brake disc with a stable friction coefficient.
The method results in a brake disc with a continuous friction film, reduced wear, and improved braking stability, addressing friction coefficient instability and wear issues.
Smart Images

Figure CN119219423A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brake material preparation, and in particular to a friction coefficient-stabilized carbon-ceramic brake disc and a preparation method thereof. Background Art
[0002] As a new type of brake material, ceramic matrix composite materials have the characteristics of stable friction coefficient, small friction loss, large braking range and long life compared with traditional materials. Among them, C / SiC materials have better performance than brake materials made of C / C materials and are more adaptable to the environment. As a brake material, ceramic matrix composite materials have greatly increased the operating temperature, reduced the volume of the brake system, and improved the safety of the whole vehicle. As a new generation of brake materials, it has broad prospects.
[0003] The microstructure of carbon-ceramic composite brake materials includes carbon fiber reinforcement phase, carbon matrix, SiC ceramic matrix and a small amount of residual Si. The SiC ceramic phase is a hard phase, and its function is to increase the friction coefficient. However, when the SiC content on the friction surface is too high, a "plowing" effect is produced, which accelerates wear. The Si phase on the friction surface and near the surface will melt due to excessive temperature during the braking process, resulting in adhesive wear, which seriously affects the safety of braking. And because SiC and Si have good wear resistance, it is difficult for the brake disc to form a stable friction film during the braking process, which has a great impact on the stability of the friction coefficient and the smoothness of braking. Adding fillers to modify the matrix is an effective way to improve the friction performance of carbon-ceramic composite materials. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a carbon-ceramic brake disc with a stable friction coefficient and a preparation method thereof, so as to solve the problems of friction coefficient jitter, unstable braking and large wear of existing carbon-ceramic brake discs during braking.
[0005] The technical solution of the present invention to solve the above technical problem is as follows: a method for preparing a carbon-ceramic brake disc with a stable friction coefficient is provided, comprising the following steps:
[0006] (1) adding resin, organic solvent and curing agent to the filler, mixing them evenly to prepare slurry;
[0007] (2) impregnating the carbon fiber preform with the slurry obtained in step (1), and then curing and cracking the preform to obtain a carbon / carbon blank with filler;
[0008] (3) The carbon / carbon blank with filler obtained in step (2) is mechanically processed to obtain a carbon / carbon brake disc, and then ceramicized by a reaction infiltration method, and then fine-processed to obtain a ceramic brake disc with a stable friction coefficient.
[0009] On the basis of the above technical solution, the present invention can also be improved as follows:
[0010] Furthermore, in step (1), the filler and the dispersant are mixed, subjected to ultrasonic treatment, and then the resin, the organic solvent and the curing agent are added.
[0011] Furthermore, the dispersant is ethanol or acetone.
[0012] Furthermore, the mass ratio of filler to dispersant is 1:45-55
[0013] Furthermore, the mass ratio of the filler to the dispersant is 1:50.
[0014] Furthermore, ultrasonic treatment was performed for 25-35 min.
[0015] Furthermore, ultrasonic treatment was performed for 30 min.
[0016] Furthermore, in step (1), the mass ratio of filler, resin and organic solvent is 5-30:20-50:50-70.
[0017] Furthermore, in step (1), the mass of the curing agent is 5-15% of the mass of the resin.
[0018] Furthermore, in step (1), the filler is multi-walled carbon nanotubes, graphite powder or molybdenum disulfide.
[0019] The beneficial effects of adopting the above further technical solution are: adding excess carbon in the form of CNTs to the C / C preform can significantly improve the infiltration efficiency of Si, thereby improving the density of the C-SiC composite material and the uniformity of the microstructure to obtain better friction performance; in addition, unreacted CNTs and lower residual porosity can improve the fracture strength of the material. Graphite powder can slow down the shrinkage of the matrix and increase the carbon yield. It is easy to form a layer of graphite film with friction reduction and lubrication on the surface of the dual parts, so that the friction becomes friction between the two graphite films, slowing down the direct contact of the friction surface, significantly reducing wear, and stabilizing the friction coefficient. The addition of molybdenum disulfide is conducive to improving the density of the material, improving the surface roughness of the friction material, effectively reducing the pull-out and breakage of the fiber during the wear process, and greatly reducing the wear rate.
[0020] Furthermore, the particle size of the graphite powder was 1 μm.
[0021] Furthermore, in step (1), the resin is a phenolic resin or an epoxy resin.
[0022] Furthermore, in step (1), the organic solvent is ethanol or acetone.
[0023] Furthermore, in step (1), the curing agent is hexamethylenetetramine.
[0024] Furthermore, in step (1), stirring is performed at 500-700 r / min for 3-5 hours to complete the mixing process.
[0025] Furthermore, in step (1), stirring is performed at 600 r / min for 4 h to complete the mixing process.
[0026] Furthermore, in step (2), the carbon fiber preform is cleaned and dried before being impregnated.
[0027] Further, ultrasonication is performed in water for 0.8-1.5 h to complete the cleaning process.
[0028] Further, drying is carried out at 75-85°C for 10-15h.
[0029] Further, it was dried at 80°C for 12h.
[0030] Furthermore, in step (2), the impregnation is performed under vacuum conditions for 0.5-1 hour, and then under pressure conditions for 0.5-1 hour to complete the impregnation process.
[0031] Further, the immersion was performed under a pressure condition of 0.7-0.9 MPa.
[0032] Furthermore, the immersion was carried out under a pressure of 0.8 MPa.
[0033] Furthermore, in step (2), the curing is performed at 60-80°C for 1-2 hours, then at 90-110°C for 1-2 hours, and then at 120-150°C for 3-5 hours to complete the entire curing process.
[0034] Furthermore, in step (2), the curing is performed at 80° C. for 1 hour, then at 100° C. for 1 hour, and then at 150° C. for 4 hours to complete the entire curing process.
[0035] Furthermore, in step (2), the pyrolysis is carried out at 800-1200° C. for 1-3 h.
[0036] Furthermore, in step (2), the pyrolysis is carried out at 1000° C. for 3 h.
[0037] Further, the mixture is heated to the cracking temperature at a rate of 8-12°C / min.
[0038] Further, the mixture was heated to the cracking temperature at a rate of 10°C / min.
[0039] Furthermore, in step (2), the carbon fiber preform is a three-dimensional needle-punched carbon fiber preform.
[0040] Further, in step (2), the density of the carbon / carbon blank with filler is 1.3 g / cm 3 .
[0041] Furthermore, in step (3), silicon powder or ferrosilicon powder is used for ceramic treatment.
[0042] Furthermore, the ferrosilicon powder is a mixture of Si and Fe in a mass ratio of 80:20, the average particle size of Si is 50 μm, and the average particle size of Fe is 100 μm.
[0043] Furthermore, in step (3), a ceramic treatment is performed at 1500-1800° C. for 2-6 hours.
[0044] The invention also provides a friction coefficient-stabilized carbon-ceramic brake disc prepared by the method.
[0045] The present invention has the following beneficial effects:
[0046] 1. The method of the present invention introduces the filler into the carbon-carbon body by slurry impregnation before RMI, and then ceramicizes it by reactive melt infiltration (RMI) to obtain a carbon-ceramic brake disc with a continuous friction film on the surface, good wear rate and good braking stability.
[0047] 2. The PIP (impregnation-cracking) process and the addition of fillers in the present invention can slow down the volume shrinkage of the matrix, improve the carbon yield, increase the density, reduce the wear of the carbon-ceramic brake disc during braking, obtain a large-area continuous friction film, improve the braking stability of the brake disc, obtain a friction coefficient with high stability, and solve the problems of friction coefficient jitter, unstable braking, and large wear of the carbon-ceramic brake disc during braking. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The morphology of the carbon ceramic brake disc prepared in Example 1 after bench testing;
[0049] Figure 2 This is the morphology of the carbon ceramic brake disc prepared in Comparative Example 1 after bench testing;
[0050] Figure 3 This is the friction curve of the brake disc in stages 1-3 of Example 1;
[0051] Figure 4 This is the friction curve of the brake disc in stage 4.1-4.3 of Example 1;
[0052] Figure 5 This is the friction curve of the brake disc in stage 4.4-5 of Example 1;
[0053] Figure 6 This is the friction curve of the brake disc in stage 6-8 of Example 1;
[0054] Figure 7 This is the friction curve of the brake disc in stage 1-3 of comparative example 1;
[0055] Figure 8 This is the friction curve of the brake disc in stage 4.1-4.3 of comparative example 1;
[0056] Fig. 9 This is the friction curve of the brake disc in stage 4.4-5 of comparative example 1;
[0057] Fig.10 This is the friction curve of the brake disc in stage 6-8 of comparative example 1. DETAILED DESCRIPTION
[0058] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0059] Embodiment 1:
[0060] A friction coefficient-stabilized carbon-ceramic brake disc, the preparation method of which comprises the following steps:
[0061] (1) A filler (graphite powder with a particle size of 1 μm) and a dispersant (acetone) were mixed in a mass ratio of 1:50, subjected to ultrasonic treatment for 30 min, and then a resin (phenolic resin), an organic solvent (ethanol) and a curing agent (hexamethylenetetramine) were added, and stirred for 4 h with a folding blade stirrer at a speed of 600 r / min to mix evenly to obtain a slurry;
[0062] The mass ratio of filler, resin and organic solvent is 25:30:60; the mass of curing agent is 10% of the mass of resin;
[0063] (2) The three-dimensional needle-punched carbon fiber preform is soaked in clean water for ultrasonic cleaning for 1 hour, placed in a blast oven at 80°C for drying for 12 hours, and then impregnated with the slurry obtained in step (1), first vacuum impregnated for 0.5 hours, then nitrogen is introduced, and the pressure is maintained for 0.5 hours after the pressure reaches 0.8 MPa to complete the impregnation process; the impregnated preform is taken out, first cured at 80°C for 1 hour, then cured at 100°C for 1 hour, and then cured at 150°C for 4 hours to complete the curing process; the cured blank is placed in a high-temperature furnace, heated to 1000°C at a constant heating rate of 10°C / min, kept warm for 3 hours, and cracked to obtain a carbon / carbon blank with filler (density reaches 1.3 g / cm 3 );
[0064] (3) The carbon / carbon blank with filler obtained in step (2) is machined to obtain a carbon / carbon brake disc, and then siliconized at 1650° C. by reactive melt infiltration (RMI), ceramicized for 3 h, cooled in the furnace, and then fine-machined to obtain a ceramic brake disc with a stable friction coefficient.
[0065] Embodiment 2:
[0066] A friction coefficient-stabilized carbon-ceramic brake disc, the preparation method of which comprises the following steps:
[0067] (1) The filler (multi-walled carbon nanotubes) and the dispersant (ethanol) were mixed in a mass ratio of 1:45, subjected to ultrasonic treatment for 25 min, and then the resin (epoxy resin), the organic solvent (ethanol) and the curing agent (hexamethylenetetramine) were added, and stirred for 5 h with a folding blade stirrer at a speed of 500 r / min to mix evenly to obtain a slurry;
[0068] The mass ratio of filler, resin and organic solvent is 5:20:50; the mass of curing agent is 5% of the mass of resin;
[0069] (2) The three-dimensional needle-punched carbon fiber preform is soaked in clean water for ultrasonic cleaning for 0.8 h, placed in a 75°C blast oven for drying for 15 h, and then impregnated with the slurry obtained in step (1), first vacuum impregnated for 0.7 h, then nitrogen is introduced, and the pressure is maintained for 0.7 h after the pressure reaches 0.7 MPa to complete the impregnation process; the impregnated preform is taken out, first cured at 60°C for 2 h, then cured at 90°C for 2 h, and then cured at 120°C for 5 h to complete the curing process; the cured blank is placed in a high-temperature furnace, heated to 800°C at a constant heating rate of 8°C / min, kept warm for 2.9 h, and cracked to obtain a carbon / carbon blank with filler (density reaches 1.3 g / cm 3 );
[0070] (3) The carbon / carbon blank with filler obtained in step (2) is mechanically processed to obtain a carbon / carbon brake disc, and then siliconized at 1500° C. by a reactive infiltration method, ceramicized for 6 hours, cooled in the furnace, and then fine-processed to obtain a ceramic brake disc with a stable friction coefficient.
[0071] Embodiment 3:
[0072] A friction coefficient-stabilized carbon-ceramic brake disc, the preparation method of which comprises the following steps:
[0073] (1) A filler (molybdenum disulfide) and a dispersant (ethanol) were mixed in a mass ratio of 1:55, subjected to ultrasonic treatment for 35 minutes, and then a resin (phenolic resin), an organic solvent (ethanol) and a curing agent (hexamethylenetetramine) were added, and stirred for 3 hours with a folding blade stirrer at a speed of 700 r / min to mix evenly to obtain a slurry;
[0074] The mass ratio of filler, resin and organic solvent is 30:50:70; the mass of curing agent is 15% of the mass of resin;
[0075] (2) The three-dimensional needle-punched carbon fiber preform is soaked in clean water for ultrasonic cleaning for 1.5 hours, placed in a blast oven at 85°C for drying for 10 hours, and then impregnated with the slurry obtained in step (1), first vacuum impregnated for 1 hour, then nitrogen is introduced, and the pressure is maintained for 1 hour after the pressure reaches 0.9 MPa to complete the impregnation process; the impregnated preform is taken out, first cured at 80°C for 1 hour, then cured at 110°C for 1 hour, and then cured at 150°C for 3 hours to complete the curing process; the cured blank is placed in a high-temperature furnace, heated to 1200°C at a constant heating rate of 12°C / min, kept warm for 1 hour, and cracked to obtain a carbon / carbon blank with filler (density reaches 1.3 g / cm 3 );
[0076] (3) The carbon / carbon blank with filler obtained in step (2) is machined to obtain a carbon / carbon brake disc, and then silicon-iron powder (the mass ratio of Si to Fe is 80:20, the average particle size of Si powder is 50 μm, and the average particle size of Fe powder is 100 μm) is infiltrated at 1800°C by a reactive infiltration method, ceramicized for 2 hours, cooled in the furnace, and then fine-machined to obtain a ceramic brake disc with a stable friction coefficient.
[0077] Comparative Example 1:
[0078] A carbon ceramic brake disc, the preparation method of which comprises the following steps:
[0079] In step (1), no filler and curing agent are contained, and the rest is the same as in Example 1.
[0080] Test example
[0081] The ceramic brake discs prepared in Example 1 and Comparative Example 1 were subjected to brake bench testing. The test standard was SAEJ2522-2014. The two groups of tests were conducted using the same brake pad. The friction conditions were compared by comparing the surface morphology of the brake discs after the bench test, the stability of the friction performance was compared by comparing the friction coefficient curve after the test, and the degree of wear was compared by comparing the wear amount after the bench test. The results are as follows:
[0082] 1. Friction conditions
[0083] The surface morphology of the ceramic brake disc after bench test is shown in Figure 1-2 .
[0084] Depend on Figure 1-2It can be seen that after the carbon ceramic brake disc prepared in Example 1 was tested, the disc surface was smooth and complete, the scratches were small, there were no large and deep grooves, and there was an obvious friction film on the disc surface. This is because during the friction experiment, the soft graphite particles adjacent to the friction surface will be continuously squeezed onto the surface, and smeared on the friction surface layer by layer through the friction of the dual discs, and it is very easy to form a stable friction film on the friction surface.
[0085] After the bench test of the carbon ceramic brake disc prepared in Comparative Example 1, the disc surface had deep wear marks, severe wear, 45° inclined grooves, and no continuous large-area friction film appeared on the surface.
[0086] 2. Stability of friction performance
[0087] The friction coefficient curve of the ceramic brake disc after bench test is shown in Figure 3-10 (Under the SAE J255 standard, red is the temperature curve, green is the pressure curve, blue is the friction coefficient curve, and the black dot is the average friction coefficient).
[0088] Depend on Figure 3-10 It can be seen that the carbon-ceramic brake disc prepared in Example 1 has a much improved braking curve stability during the bench test. This is because the graphite particles spread on the friction surface and remain unchanged under certain conditions, which can play a stable lubricating role and make the friction coefficient of the material tend to change steadily.
[0089] The friction curve of the carbon ceramic brake disc obtained in comparative example 1 after bench testing has a large jitter in a single friction curve, which causes the friction coefficient to change during each braking process, resulting in brake jitter, eccentric wear and other phenomena.
[0090] 3. Degree of wear
[0091] The wear amount of the ceramic brake disc after the bench test is shown in Table 1.
[0092] Table 1 Wear amount of bench test
[0093] project Brake disc thickness before test / mm Thickness of brake disc after test / mm Wear amount / mm Example 1 27.980 27.975 0.005 Comparative Example 1 28.010 27.920 0.090
[0094] As can be seen from Table 1, the wear amount of the carbon-ceramic brake disc prepared in Example 1 of the present invention is much lower than that in Comparative Example 1, with only 0.005 mm of wear, which greatly improves the service life of the carbon-ceramic brake disc.
[0095] The carbon ceramic brake disc obtained in Comparative Example 1 has a relatively large wear amount of 0.090 mm, which will directly affect the service life of the brake disc.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a friction coefficient-stabilized carbon-ceramic brake disc, characterized in that: The following steps are involved: (1) adding resin, organic solvent and curing agent to the filler, mixing them evenly to prepare slurry; (2) impregnating the carbon fiber preform with the slurry obtained in step (1), and then curing and cracking the preform to obtain a carbon / carbon blank with filler; (3) The carbon / carbon blank with filler obtained in step (2) is mechanically processed to obtain a carbon / carbon brake disc, and then ceramicized by a reaction infiltration method, and then fine-processed to obtain a ceramic brake disc with a stable friction coefficient.
2. The method for preparing a friction coefficient-stabilized carbon-ceramic brake disc according to claim 1, characterized in that: In step (1), the filler and the dispersant are mixed, subjected to ultrasonic treatment, and then the resin, the organic solvent and the curing agent are added.
3. The method for preparing a friction coefficient-stabilized carbon-ceramic brake disc according to claim 1, characterized in that: In step (1), the mass ratio of filler, resin and organic solvent is 5-30:20-50:50-70.
4. The method for preparing a friction coefficient-stabilized carbon-ceramic brake disc according to claim 1, characterized in that: In step (1), the mass of the curing agent is 5-15% of the mass of the resin.
5. The method for preparing a friction coefficient-stabilized carbon-ceramic brake disc according to claim 1, characterized in that: In step (1), the filler is multi-walled carbon nanotubes, graphite powder or molybdenum disulfide.
6. The method for preparing a friction coefficient-stabilized carbon-ceramic brake disc according to claim 1, characterized in that: In step (2), the impregnation is carried out under vacuum conditions for 0.5-1 hour, and then under pressure conditions for 0.5-1 hour to complete the impregnation process.
7. The method for preparing a friction coefficient-stabilized carbon-ceramic brake disc according to claim 1, characterized in that: In step (2), the curing is carried out at 60-80°C for 1-2 hours, then at 90-110°C for 1-2 hours, and then at 120-150°C for 3-5 hours to complete the entire curing process.
8. The method for preparing a friction coefficient-stabilized carbon-ceramic brake disc according to claim 1, characterized in that: In step (2), the pyrolysis is carried out at 800-1200° C. for 1-3 h.
9. The method for preparing a friction coefficient-stabilized carbon-ceramic brake disc according to claim 1, characterized in that: In step (3), silicon powder or ferrosilicon powder is used for ceramic treatment.
10. A friction coefficient-stabilized carbon-ceramic brake disc obtained by the method for preparing a friction coefficient-stabilized carbon-ceramic brake disc according to any one of claims 1 to 9.
Citation Information
Patent Citations
Powder-metallurgical automobile brake pad and preparation method thereof
CN106282815A
Carbon-carbon or carbon-ceramic composite material net tire prefabricated body and product and preparation method thereof
CN113149685A
Method for preparing carbon-ceramic brake disc by combining porous carbon / carbon green body with RMI
CN117923939A
Improvements in or relating to disc brakes
GB2428759A
Friction pairing for parking brakes in motor vehicles
US20050072637A1
